Comparison of argentinean saint louis encephalitis virus non-epidemic and epidemic strain infections in an avian model. - Luis Adrián Diaz; Nicole M Nemeth; Richard A Bowen; Walter R Almiron; Marta S Contigiani (Public Library of Science (PLoS), 2011)
St. Louis encephalitis virus (SLEV, Flavivirus, Flaviviridae) is an emerging mosquito-borne pathogen in South America, with human SLEV encephalitis cases reported in Argentina and Brazil. Genotype III strains of SLEV were isolated from Culex quinquefasciatus mosquitoes in Cordoba, Argentina in 2005, during the largest SLEV outbreak ever reported in South America. The present study tested the hypothesis that the recent, epidemic SLEV strain exhibits greater virulence in birds as compared with a non-epidemic genotype III strain isolated from mosquitoes in Santa Fe Province 27 years earlier. The observed differences in infection parameters between adult House sparrows (Passer domesticus) that were needle-inoculated with either the epidemic or historic SLEV strain were not statistically significant. However, only the House sparrows that were infected with the epidemic strain achieved infectious-level viremia titers sufficient to infect Cx. spp. mosquitoes vectors. Furthermore, the vertebrate reservoir competence index values indicated an approximately 3-fold increase in amplification potential of House sparrows infected with the epidemic strain when pre-existing flavivirus-reactive antibodies were present, suggesting the possibility that antibody-dependent enhancement may increase the risk of avian-amplified transmission of SLEV in South America.